Proceedings of the Fifth International Conference on Geotextiles, Geomembranes and Related products, Singapore, 5-9 September 1994 - International Conference on Geotextiles, Geomembranes and Related products (5th : 1994 : Singapore); Karunaratne, G. P.; Chew, S. H.; Wong, K. S.; International Geotextile Society. Southeast Asia Chapter (Singapore : SEAC-IGS, 1994)
Vol.1. Reinforcement applications and related research -- vol.2. Hydraulic applications and related research -- vol.3. Environmental applications, geosynthetics testing and related research -- vol.4. Post conference proceedings